National summary reports on pesticide residue analysis performed in 2019. Issue 4 (7th April 2021) - ,
Abstract : In accordance with Article 31 of Regulation (EC) No. 396/2005, European Union (EU) Member States provide to the European Food Safety Authority (EFSA) the results of their official controls on pesticide residues in food. In this framework, the EU Member States, Iceland and Norway provided further information in the form of explanatory text outlining main findings of their control activities during the reference year. This Technical report is the compilation of those contributions of the reporting countries. Abstract : This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2021.6491/full